ON bi- INTUITIONSTIC TOPOLOGICAL SPACE - Taha H. Jassim; Zenah T. Abdulqader; Hiba O. Mousa (Tikrit Journal of Pure Science)
In this paper we introduce a new definition is called bi- intuitionistic topological space and from this concept we present some kinds of closed set (semi –closed, pre-closed ,β-closed ,α-closed) setes in bi- intuitionistic topological space, define generalized closed set (sg-closed ,gs-closed ,gp-closed, gα-closed , αg- closed , gβ-closed) sets in bi - intuitionistic topological space and give relationship among them , we introduce the definition of Tgs-space in bi- intuitionistic topological space and  from  this consept we get new results